ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KREDIT OLEH PELAKU USAHA KECIL MENENGAH PADA DEBITUR BANK PERKREDITAN RAKYAT KOTA BATAM - Efriyenty, Dian; E Janrosl, Viola Syukrina (Aksara Public, 2017)
This study aims to determine the effect of interest rate, collateral, nominal credit and banking services to decision-making credit by small businesses on the debtor BPR medium in Batam from year 2012 to 2016. The sampling method used this research is non probability sampling with purposive sampling. The sample in this study is small and medium enterprises BPR borrowers in Batam which totaled 86. The results of the test F interest rates, guarantees, loans and bank services nominal influence on decision-making loans. The results of the t test and the nominal interest rate loans significantly influence the decision-making loans. While guarantees and bank services does not affect the decision-making due credit loan capital known to the public with no hard collateral requirements. So also in terms of service, communication and administration at BPR lack of providing information to the debtor UKM quick and responsive in addressing complaints of UKM.